The Influence of The Use of Audio-Visual Media on The Ability of Fraction Calculation Operations of Grade IV Students of SD Negeri 4 Amparita Sidrap - Azhari, Ayu; Suwendra, I Wayan (Jayapangus Press, 2024)
This study examines the effect of the use of audio-visual media on the ability of fraction calculation operations of fourth grade students of SD Negeri 4 Amparita. The main problem studied is whether there is a positive influence of audio-visual media on the ability of fraction calculation operations of fourth grade students of SD Negeri 4 Amparita. This study is an experimental research that aims to determine whether there is a positive effect of audiovisual media on the ability of fraction calculation operations of fourth grade students of SD Negeri 4 Amparita Sidrap on the material of addition and subtraction of fractions. This research uses a quantitative approach. This study consists of two variables, namely audiovisual media and conventional models as independent variables and students' fraction calculation operation skills as the dependent variable, using the Randomized Subject Pretest-Posttest Control Group Design research design. The population in this study were all 4th grade students of SD Negeri 4 Amparita consisting of 1 class with a total sample of 42 people. The research sample of class IVA as an experimental class with 21 students and Class IVB with 21 students who were selected by Random Class. The data obtained were analyzed with descriptive statistics and inferential statistics. The results of descriptive analysis showed that the average value of fraction calculation ability of experimental class students was 75.71 and the average value of fraction calculation ability of control class students was 60.48. The learning completeness of experimental class students was 85.95% while the learning completeness of control class students was 47.61%. Inferential statistical analysis to test the hypothesis through Independent Sample T-tests obtained the value of -t count < - t table (-3.678 < -2.021) or t count > t table (3.678 > 2.021) thus H0 is rejected and H1 is accepted. In this case, audio-visual media has a positive effect on the ability of fraction calculation operations of fourth grade students of SD Negeri 4 Amparita Sidrap.